2010
DOI: 10.2174/1874210601004010140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial-Antibiofilm Activity of a Hydrogen Peroxide Decontaminating System Used in Dental Unit Water Lines

Abstract: A dental unit water line (DUWL) equipped with a device designed to automatically and continually flush a bacteriostatic solution of hydrogen peroxide (WHE) and a discontinuous disinfecting system (BIOSTER) was evaluated. In the first instance a preliminary sensitivity test on a large number of microorganisms (bacteria and fungi) was tried with a H2O2 range from 100 to 800 ppm. The bacteria frequently reported in DUWL (including Pseudomonas spp, Streptococcus spp., Staphylococcus spp., E. coli) and some periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
3
14
1
6
Order By: Relevance
“…However, we were able to effectively eradicate the bacteria within a preformed biofilm. Our results differ from previous works evaluating the same agents to disrupt preformed biofilms of environmental and human bacterial isolates (51)(52)(53)(54)(55)(56)(57)64). In the current study, preformed biofilm biomass was reduced by Ͼ80%, and the mean log of CFU was decreased by Ͼ3 log in the laboratory control strains of E. coli, P. aeruginosa, and K. pneumoniae.…”
Section: Figcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we were able to effectively eradicate the bacteria within a preformed biofilm. Our results differ from previous works evaluating the same agents to disrupt preformed biofilms of environmental and human bacterial isolates (51)(52)(53)(54)(55)(56)(57)64). In the current study, preformed biofilm biomass was reduced by Ͼ80%, and the mean log of CFU was decreased by Ͼ3 log in the laboratory control strains of E. coli, P. aeruginosa, and K. pneumoniae.…”
Section: Figcontrasting
confidence: 99%
“…The resistance of P. aeruginosa to hydrogen peroxide is mediated through the production of catalase enzyme that inactivates hydrogen peroxide (56). Strains of E. coli associated with dental hardware are relatively susceptible to disruption of a preformed biofilm and killing with hydrogen peroxide (57), and a similar effect was observed in the current study, as E. coli preformed biofilms were relatively easy to disrupt and kill the bacteria residing within the biofilm. It should also be noted that the in vitro effects of hydrogen peroxide observed in the current study might not be observed in vivo due to inactivation from catalases produced by host tissues (58).…”
Section: Figsupporting
confidence: 78%
“…The disinfectant effectiveness of apple vinegar and hydrogen peroxide found in this research corroborates with the studies of Perez et al . and Orrù et al ,. especially considering the reduction of E. coli viability with hydrogen peroxide treatment.…”
Section: Discussionsupporting
confidence: 93%
“…In view of low toxicity, low cost and a viable home-use application, apple vinegar and hydrogen peroxide showed the best antimicrobial activity against reference strains in screening tests (agar well diffusion and MIC/MMC evaluation). Vinegar and hydrogen peroxide have been suggested as interesting alternatives for the disinfection of other materials 19,20,[25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine 13,14,34) , tetraacetyl enediamine 38) , hydrogen peroxide 24,33) , strong-type acidic electrolyzed water 20) , bleach, and other chemicals 27) have been used in dental unit waterline decontamination. In our study, we found MRSA and P. aeruginosa in the control DUWS by PCR.…”
Section: Discussionmentioning
confidence: 99%